Overnight extubation and risk of extubation failure in patients in the pediatric intensive care unit: an exploratory review - Payán-Salcedo, Harold Andrés; Sandoval, Valentina Ortiz; Castro Ibarguen, Bivian Dairovy; Ramírez, Yina Lisbeth; Cortés González, Sergio Leonardo; Arzayus-Patiño, Leonardo (Frontiers in Pediatrics, 2025)
Background/objectivesExtubation in pediatric intensive care units (PICUs) requires care and thoroughness to minimize risks of extubation failure, systemic complications, and mortality. Up to 20% of patients in the PICU experience extubation failure, resulting in reintubation, longer hospital stays, and higher healthcare costs. Currently, no reviews have synthesized findings on the effect of overnight extubation and its association with extubation failure.MethodsThis exploratory review was conducted based on the Joanna Briggs Institute methodology and PRISMA extension for scoping reviews guidelines. We analyzed studies collected from databases such as PubMed, Scopus, Web of Science, Science Direct, VHL Regional Portal, and Google Scholar using MeSH terms, Boolean operators, and a search strategy based on population, concept, and context (PCC). Studies that evaluated the impact of overnight extubation in the PICU were included, with the primary outcome being the association with the risk of extubation failure.ResultsT Results: of 275 records identified, five studies met the inclusion criteria. Four studies found no significant association between overnight extubation and extubation failure, whereas one study with a larger sample reported a higher risk of reintubation during nighttime extubation. Overall, the findings revealed heterogeneous results influenced by population type, clinical context, and organizational factors.ConclusionsThe available evidence does not consistently demonstrate that overnight extubation increases the risk of failure; however, some studies suggest that patient complexity and contextual factors may modify this relationship. Therefore, extubation decisions should be individualized according to clinical stability and available resources rather than based solely on the time of day, underscoring the need for prospective and standardized studies in this field.